Design and optimization of a crossflow tube reactor system for hydrogen production by combining ethanol steam reforming and water gas shift reaction. (15th February 2023) - Chen, Wei-Hsin; Lu, Chen-Yu; Chou, Wei-Shan; Kumar Sharma, Amit; Saravanakumar, Ayyadurai; Tran, Khanh-Quang
Graphical abstract: Highlights: A crossflow tube reactor system is designed for hydrogen production from ethanol. The crossflow tube reaction system consists of ethanol steam reforming and water gas shift reaction. The steam/ethanol (S/E) ratio of 3 is optimal for hydrogen production and CO reduction. The effect of the tube diameter on catalyst cost is higher than that of the catalyst thickness. The optimized system intensifies H2 yield by 1.05 times and improves CO reduction by 27.38%. Abstract: Crossflow tube reactors with crossflow configuration are considered a special design for hydrogen production via ethanol steam reforming with less catalyst than conventional packed bed reactors. However, the results showed that crossflow tube reactors would produce an elevated concentration of carbon monoxide, which has a detrimental effect on further applications of the product gas from steam reforming, such as hydrogen purification. This drawback can be diminished by integrating a water gas shift reaction unit into the steam reformer. This study's combined system is numerically investigated for hydrogen production and enrichment. The results show that low reaction temperatures are favorable for hydrogen production. The steam/ethanol (S/E) ratio of 3 is optimal for hydrogen production and CO reduction in the system combined with ethanol steam reforming and water gas shift reaction. Both variations in the catalytic tube diameter and the catalyst thickness positively affect hydrogen production. However, the effect of the tube diameter is higher than that of the catalyst thickness. This study also uses a parametric sweep associated with the evolutionary computation of bound optimization by quadratic approximation (BOBYQA) method to optimize the system's tube arrangement. The optimized system intensifies H2 yield by 1.05 times and improves CO reduction by 37.71% compared to ethanol steam reforming alone.